(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the outcome of K-wire fixation of Clavicular fracture in terms of union rates and complication profile. Study Design: Retrospective case series study. Place and Duration of Study: This study was carried out at DHQ teaching hospital Abbottabad and Mansehra from March 2009 to Feb 2011. Materials and Methods: Forty five adult patients with displaced mid clavicular fractures treated with K-wire fixation in a standard Supine position were included in this study. Results: Out of 45 patients, non union occurred in only two, Implant failure occurred in the same two cases. Most of the complications were of minor nature consisting of superficial wound infection 2, delayed union 4 and pin prominence at insertion site 10. No major nerve or vascular injuries occurred. Conclusion: Intra medullary K-wire fixation of displaced mid clavicular fracture with protection in early post operative period is a safe and simple procedure, achieving good union rates without major complications.